The origin of semidiurnal neutral wind oscillations in the high-latitude ionospheric dynamo region - Günzkofer, Florian Ludwig; Pokhotelov, Dimitry; Stober, G.; Liu, Huixin; Liu, Hanli; Mitchell, N.; Tjulin, Anders; Borries, Claudia (2023)
Tidal neutral wind oscillations in the high latitude ionospheric dynamo/transition region can be either in situ forced or propagate there from lower atmospheric layers. Investigating the complex mixing of tidal modes allows to determine the solar, geomagnetic and atmospheric impact on the transition region dynamics. In classical tidal theory, semidiurnal tides forced by UV and infrared absorption in lower atmospheric regions propagate upwards and are the dominant tidal mode up to about 120 km. Above that, diurnal tidal modes forced in situ by EUV absorption and ion drag due to the polar plasma convection are assumed to be dominant. We analyze a 22 day long measurement campaign with the EISCAT UHF incoherent scatter radar during September 2005. The beam-swinging experiment allows to obtain neutral winds from 96 - 142 km altitude which are combined with simultaneous meteor radar measurements. An Adaptive Spectral Filtering technique is applied to determine tidal amplitudes and phases. The zonal wind showed the expected transition from semidiurnal to diurnal oscillations at about 120 km. The meridional wind showed a more complex tidal structuring with dominant 12h oscillations below 110 km and above 130 km. General Circulation Model runs with different forcing settings are analyzed to determine the origin of these high altitude semidiurnal oscillations. The measured asymmetry of tidal amplitudes in zonal and meridional winds is found in all investigated model runs. It is shown that atmospheric tides have no influence on tidal oscillations above 120 km. Polar ion convection and EUV absorption both appear to contribute to the observed strong semidiurnal oscillations above 130 km.